2022
DOI: 10.55629/pakjpathol.v33i2.697
|View full text |Cite
|
Sign up to set email alerts
|

High Fluorescence Lymphocyte Count as an Early Predictor of Severe Thrombocytopenia in Dengue Infection

Abstract: Objective: Dengue infection (DI) is the most common arthropod-borne viral disease with symptoms ranging from mild flu like illness to fatal hemorrhagic fever. Thrombocytopenia is one of the common manifestations of dengue which can lead to life threatening bleeding. Currently, there is no validated test available that can predict the severity of thrombocytopenia in a dengue patient. Dengue has been well associated with presence of high fluorescence lymphocytes in the peripheral blood. High fluorescence lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This difference may be due to our hospital that caters more female patients. 13,14 Another study conducted at Lahore and reported mean age of patients was 45 years which is consistent with our study. 14 Maximum number of cases were referred from OPD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This difference may be due to our hospital that caters more female patients. 13,14 Another study conducted at Lahore and reported mean age of patients was 45 years which is consistent with our study. 14 Maximum number of cases were referred from OPD.…”
Section: Discussionsupporting
confidence: 91%
“…Due to country's geographic location, changing climate, growing population, unplanned urbanization, and lack of effective vector control programs, dengue has become endemic in Pakistan. 13,14 According to our study, females are more prone to dengue as compared to male. Most of the studies reported that male are more affected.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation